Fecal microbiota transplantation for treating recurrent hepatic encephalopathy: Ready for clinical application? - Karakan, Tarkan (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Karakan T. Fecal microbiota transplantation for treating recurrent hepatic encephalopathy: one step further? Turk J Gastroenterol 2017; 28: 425-6.